Analisis peran total factor productivity pada industri manufaktur Indonesia - Lincoln Arsyad; Mursal Salam (Economic Journal of Emerging Markets, 1998)
In the last 15 years, Indonesia's manufacturing sector has performed a very fast rate of growth. The question is what factors caused the rate of growth, increasing resource use or technology driven?